Omeprazole may exert both a bacteriostatic and a bacteriocidal effect on the growth of Helicobacter pylori (NCTC 11637) in vitro by inhibiting bacterial urease activity. Issue 3 (March 1998) - Mirshahi, F; Fowler, G; Patel, A; Shaw, G
Abstract : AIMS: To assess the potential antibacterial effect of omeprazole, a benzimidazole proton pump inhibitor, on the growth of Helicobacter pylori in vitro and to evaluate the effect of this compound on bacterial urease activity. METHODS: The growth of H pylori was observed in liquid culture in the presence and absence of omeprazole (0.8 mg/ml). Urease activity was evaluated in aliquots removed from two hour cultures by monitoring the initial change in absorbency at 560 nm in the presence of 0.02% phenol red. RESULTS: The minimum inhibitory concentration of omeprazole against H pylori was 0.8 mg/ml. The concentration of omeprazole required to inhibit growth was dependent on inoculum density: omeprazole (0.8 mg/ml) prevented growth from a 1 x 10(6) cfu/ml inoculum, but not from the higher inocula of 10(7) or 10(8) cfu/ml. This is the first study to demonstrate that omeprazole exerts a bacteriocidal effect against low bacterial densities and a bacteriostatic effect when bacterial density is high. When used at the onset of growth, this concentration of omeprazole has a bacteriocidal effect after four hours, although it exerts a bacteriostatic effect when added to cultures after the exponential phase. Bacterial urease activity is competitively inhibited by omeprazole in a dose dependent manner. CONCLUSION: The results suggest that omeprazole exerts both a bacteriocidal and a bacteriostatic effect against H pylori and competitively inhibits bacterial extracellular urease activity.